Modelo multicritério de apoio à decisão construtivista para avaliação do clima organizacional em uma instituição federal de ensino superior - Kihara, Ligiane Marie Shiquedoni (2021)
In the search for the development of organizations and the improvement of services provided to society, it is essential to consider the perception of the people who are part of the institution. In this sense, the assessment of the organizational climate is a management tool that allows obtaining such knowledge through the application of categories appropriate to the situation studied. In order to map and identify the concepts of organizational climate and most mentioned authors, the Knowledge Development Process - Constructivist (ProKnow-C) was used. Then, through bibliographic research, the appropriate categories were identified for the analysis of the organizational climate in a higher education institution and validated by it. The present work contemplates the construction of an organizational climate evaluation model using the Constructivist Decision Support Multicriteria Analysis methodology - MCDA-C, allowing a quantitative evaluation of its results. Regarding the concepts, this research comprised 54 years of conceptual development and, according to this study, the most cited authors were Forehand and Gilmer; followed by Gonçalves; Litwin and Stringer; Schneider and Robbins. The results obtained corresponding to the categories converged to the 12 categories defined in the work of Rizzatti (2002). It was also possible to establish the priority categories for the unfolding of the research, as well as the definition of the group of actors in the researched institution. Thus, it is concluded that it was possible to structure an organizational climate assessment to meet the particularities of a higher education institution with global level indicators, considering the value judgments of the decision makers and that allow to improve the understanding of the problems in order to propose appropriate changes to the institution, with the expectation of achieving significant effects on motivation and satisfaction, through actions, to achieve the institution's objectives.